Analysis of a Cretaceous (late Aptian) high-stress ecosystem: The Romualdo Formation of the Araripe Basin, northeastern Brazil - Fürsich, Franz T.; Custódio, Michele Andriolli; Matos, Suzana A. [UNESP]; Hethke, Manja; Quaglio, Fernanda; Warren, Lucas Veríssimo [UNESP]; Assine, Mario L. [UNESP]; Simões, Marcello Guimarães [UNESP] (Elsevier, 2019)
The Cretaceous (upper Aptian) Romualdo Formation of the Araripe Basin, northeastern Brazil, is a marine-influenced, predominantly fine-grained siliciclastic unit. In the eastern part of the basin, it corresponds to a depositional sequence composed of two transgressive-regressive cycles. Low-diversity benthic macrofaunas document high-stress conditions. Their palaeoecological and taphonomic analysis allows for the detailed reconstruction of the palaeoenvironments and of the temporal changes in the palaeoecosystem. The transgressive part of the lower cycle is a black shale with calcareous concretions that contain excellently preserved fishes and other vertebrates (the famous “Santana fossils”), but apart from abundant ostracods and rare decapod crustaceans, benthic faunal elements are very rare due to anoxic to dysoxic conditions. A low-diversity parautochthonous molluscan fauna of small bivalves and gastropods records fluctuating dysoxic conditions during early regression. Towards the top of the measured sections (late regression), thin gastropod shell beds become conspicuous. At the top of the sections decimetre-thick shell concentrations show signs of reworking and a greater marine influence (transgressive part of the upper cycle). The distribution pattern of three benthic associations and two assemblages is almost equally shaped by three environmental parameters: The low overall species diversity, small size of the fauna, and the lack of stenohaline elements suggest lowered and fluctuating salinity conditions. Fluctuating redox conditions with anoxia to dysoxia, identified especially in the lower parts of the succession, and substrate were the other two factors shaping the faunal distribution. The late Aptian sedimentary and faunal history of the eastern part of the basin indicates restricted marine influence, coupled with increasing freshwater input during phases of sea-level lowstand, and low-energy conditions offshore, which led to widespread anoxia, especially in the lower part of the formation. Thus, palaeoecological analyses are an excellent tool to disentangle the various environmental parameters that shaped the palaeoenvironments of the basin, to understand more closely its Fossil-Lagerstätten, and to corroborate and fine-tune the sequence stratigraphic framework.
Keywords: Benthic palaeoecology; Lower Cretaceous; Santana Group; Taphonomy